2020
DOI: 10.3389/fvets.2020.00621
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load and Cell Tropism During Early Latent Equid Herpesvirus 1 Infection Differ Over Time in Lymphoid and Neural Tissue Samples From Experimentally Infected Horses

Abstract: Upper respiratory tract infections with Equid Herpesvirus 1 (EHV-1) typically result in a peripheral blood mononuclear cell-associated viremia, which can lead to vasculopathy in the central nervous system. Primary EHV-1 infection also likely establishes latency in trigeminal ganglia (TG) via retrograde axonal transport and in respiratory tract-associated lymphatic tissue. However, latency establishment and reactivation are poorly understood. To characterize the pathogenesis of EHV-1 latency establishment and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…It is possible that this depth of next-generation sequencing is more sensitive than our qPCR assay, and it is also possible that viral transcripts are more abundant in samples than latent genomic DNA. While the trigeminal ganglia is the trademark site for EHV-1 latency, many studies have reported EHV-1 latency in lymphoid tissues and PBMCs as well as in additional ganglia and lymphoid tissues [ 3 , 4 , 5 , 6 , 7 ]. It is presumed that most horses become infected with EHV-1 at a very young age (days to weeks old) [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that this depth of next-generation sequencing is more sensitive than our qPCR assay, and it is also possible that viral transcripts are more abundant in samples than latent genomic DNA. While the trigeminal ganglia is the trademark site for EHV-1 latency, many studies have reported EHV-1 latency in lymphoid tissues and PBMCs as well as in additional ganglia and lymphoid tissues [ 3 , 4 , 5 , 6 , 7 ]. It is presumed that most horses become infected with EHV-1 at a very young age (days to weeks old) [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The classical theory of herpesvirus biology describes sensory ganglia as the primary target for latency of alphaherpesviruses and lymphocytes as the primary latency site for gammaherpesviruses [ 1 ]. While several reports have identified lymphoid tissues as a site of latency for EHV-1, genome detection in circulating PBMC via qPCR is often negative in non-clinically affected animals [ 3 , 4 , 5 , 6 , 7 , 96 ]. In contrast, EHV-2 and EHV-5 can be routinely detected in PBMC samples of healthy animals [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Latent EHV-1 was detected by PCR and recovered by co-cultivation from lymphoid tissues draining the respiratory tract of experimentally inoculated ponies ( Welch et al, 1992 ; Kydd et al, 1994 ; Slater et al, 1994a ). Additional studies stating that EHV-1 establishes latency in lymphoid tissues, failed to conclusively demonstrate the presence of LATs in these tissues ( Pusterla et al, 2010 , 2012 ; Goehring, 2017 ; Giessler et al, 2020 ). Finally, circulating T lymphocytes have been defined as a predominant site of EHV-1 latency.…”
Section: The Pathogenesis Of Ehv-1mentioning
confidence: 99%